The Impact of Blayomterc Special Exercises to Develop Muscle Power on the Movement of Defensive Basketball Player Ages (18 years) and less - Mohammed, Laith (Journal of Physical Education, 2012)
The study consists of five chapters: The first chapter presents the development in the field of athletic training through the use of manners and methods that contribute to the development of the players physically. As is the importance of research in the use of blayomterc special exercises to develop muscle power its impact on the movement of defensive basketball player. The problem lies in component of muscle power needed to develop in terms of exercises and methods used in the training process because of the developments and progress in the levels of a game of basketball. In second chapter, the researcher dealt with some of the theoretical issues on the subject of blayomterc as well as to the component of muscle power and defensive player. In third chapter, the researcher used the experimental method on a sample of (10) players from Sulaikh Club for young and included one experimental group. The study ,in chapter fourth, presents the results were discussed and analyzed through the use of a number of statistical tools, with which the researcher to develop a component of muscle power and its impact on the performance of defensive basketball player. Finally, in chapter five, the conclusion indicates that the training by style blayomterc has been a very effective in the development of component muscle power, as well as its positive effect on the speed of movement of defensive player , as well as, the researcher recommended the need to set aside time from the days of training to develop the component of muscle power and the need to design new exercises as well as the need use of style blayomterc special for the youth because its interest for this group of